Stres Kerja dan Motivasi Kerja terhadap Turnover Intention dengan Kepuasan Kerja sebagai Variabel Intervening - Pratiwi, Indah Dian; Hasyim, Hasyim; Supriyantoro, Supriyantoro (Journal of Telenursing (JOTING), 2023)
This research aims to analyze work stress and work motivation on employee turnover intention with job satisfaction as an intervening factor at RSIA X Palembang. The method used is a quantitative causality research method to look at the factors that are related to employees' desire to leave work with a survey research design. The research results show that under work stress, work motivation influences employee turnover intention. Job stress influences job satisfaction. Work motivation has no effect on job satisfaction. Job stress influences turnover intention. Work motivation influences turnover intention. Job satisfaction has no effect on turnover intention. The conclusion was that work stress at RSIA The variables job stress and work motivation influence turnover intention together with job satisfaction as an intervening variable. The work stress variable has a negative effect on job satisfaction. The work motivation variable has no effect on job satisfaction. The work stress variable has a positive effect on turnover intention. The work motivation variable has a negative effect on turnover intention. The job satisfaction variable has no effect on turnover intention. Keywords: Satisfaction, Motivation, HR, Stress, Turnover, Turnover Intention